Relationship of Sweet Caffeinated Beverages Consumption and Sleep Quality with Nutritional Status in Adolescent - Zalda, Fathiya; Alamsyah, Putri Rahmah (Universitas Airlangga, 2024)
Overnutrition is more common among adolescents. In Indonesia, lack of physical activity, poor quality of sleep due to daily schedules, and the consumption of sweet, fatty, and fast foods are the main contributing factors. This study aimed to analyze the relationship between the frequency of consumption of sweet caffeinated beverages and sleep quality with nutritional status in adolescents in high school 5 Tambun Selatan. This study used quantitative research with observational analysis using a cross-sectional design. The sample consisted of 101 individuals randomly chosen by a simple random sampling method. Data were collected using the Food Frequency Questionnaire and Pittsburgh Sleep Quality Index with the determination of the nutritional status of adolescents obtained from Z-score BMI/U. The Chi-Square test results indicated significant correlations exist between the frequency of sweet caffeinated beverages consumption and nutritional status (p=0.045) but no significant correlations were found between sleep quality and nutritional status (p=0.797) in adolescents in high school 5 Tambun Selatan.